Permintaan Daun Pisang pada Produsen Nasi Jinggo di Kota Denpasar - DEFRY SANJAYA GUNAWAN; I WAYAN WIDYANTARA; I WAYAN BUDIASA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
The Demand for Banana Leaves by the Jinggo Rice Producers in Denpasar City This study aims to determine the number of banana leaves demand by the jinggo riceproducers in a period of one week, the factors that affect the demand of banana leaves,and to investigate the substitute of banana leaves used by sellers as a jinggo ricewrapper. The research location was in Denpasar City determined by purposivesampling. The population in this research was all of the jinggo rice sellers in DenpasarCity. The sampling technique used snowball sampling method. This research usedtabulation to find out the demand of banana leaves discussed descriptively andqualitatively and by using regression equation which is transformed to analyze theinfluencing factors. The results of this study indicate that the total number of bananaleaves demand by 40 respondents of jinggo rice sellers in Denpasar, within one week isequal to 7,822 folds or as many as 23,466 banana leaf bark. Factors affecting thedemand of banana leaves from the jinggo rice sellers in Denpasar City were the price ofbanana leaves and the amount of production, and there is no substitute for banana leavesused by the 40 jinggo rice sellers in Denpasar City.